Laporan Kasus: Ventilator Non-Invasif sebagai Salah Satu Alternatif dalam Memperbaiki Gerakan Diafragma, Arus Puncak Ekspirasi dan CO2 Akhir Ekspirasi Pasien Tuna Laring - Siti Chandra Widjanantie; Ferius Soewito (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Laringectomee may have problems on their lung compliance as a result of the diaphragm’s increasing resistance. These can cause an increase on CO2 end-tidal. Non-invasive ventilator (NIV) is theorized to improve lung compliance with the end result on CO2 end-tidal correction. This case series was made to report the effect of NIV on several lung function parameters. Three cases of laringectomees were reported. Each history, present complain was noted. Diaphragm movement at inspiration and expiration were measured using ultrasonography. Peak huff flow and CO2 end tidal were also measure before and after NIV. All patients showed improvement on diaphragm movement and CO2 end tidal. One patient showed a decrease on his peak huff flow measurement. Clinically NIV showed a good result on diaphragm compliance and CO2 end-tidal. Effect of NIV on peak huff flow was not consistent in this case series. A clinical trial with sufficient numbers of patients and a proper method is needed to give evidence whether NIV can provide significant positive effect for laringectomees.